NF-κB deficit in spinal motoneurons in patients with sporadic amyotrophic lateral sclerosis – a pilot study - Sulejczak, Dorota; Chrapusta, Stanisław J.; Dziewulska, Dorota; Rafałowska, Janina (Folia Neuropathologica, 2015)
Amyotrophic lateral sclerosis (ALS) is a fatal incurable neurodegenerative disease whose etiology is unknown and pathogenesis is still not fully understood. A great majority of its cases are sporadic. Clinical ALS signs are caused by damage and dying-out of the lower and upper motor neurons. This study was aimed at identifying possible sporadic ALS-associated aberrations in the spinal cord expression of the transcription nuclear factor κ light-chain-enhancer of activated B cells (NF-κB). NF-κB is widely distributed among various cell types, including those specific for the central nervous system (CNS), and is involved in the control of many physiological and pathological processes, including, inter alia, inflammatory response, proliferation, angiogenesis, and cell survival and death. It is constitutively expressed and its inactive form resides in the cytoplasm. After activation, it enters the cell nucleus and promotes the transcription of target genes. NF-κB is a dimer and its most common form is a heterodimer made of subunits p50 and p65. In this study, we estimated and compared by immunohistochemical means the contents of these subunits in spinal cord motoneurons in a few archival cases of sporadic ALS of varying disease duration and the respective age-matched control cases with no CNS pathology. The major goal of the study was to seek possible changes in the expression of these proteins in the course of the disease. The control cases showed a strong expression of both p50 and p65 in spinal cord motoneurons, with both cytoplasmic and nuclear localization. In contrast, the ALS cases studies revealed a considerably lower and varying intensity of specific immunohistochemical staining for the two subunits, which suggested an increased deficit of their expression linked to longer disease duration. Moreover, there was an apparent shift toward mostly cytoplasmic localization of the two subunits. These preliminary data suggest that the changes in the expression of theses NF-κB subunits may be involved in pathogenesis of sporadic ALS.